2020
DOI: 10.1016/j.intimp.2020.106924
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic approaches to curtail COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 155 publications
0
69
0
7
Order By: Relevance
“…The virus entry block was studied for acting both in the cell receptor ACE2 and directly on the virus (neutralizing antibodies [nAbs]), specifically in the S1 subunit of the S protein (218)(219)(220). Regarding the blocking of ACE2 receptors, the application of some mechanisms stand out: the soluble version of ACE2 fused to an immunoglobulin Fc domain (ACE2-Fc), RDB domain attached to Fc (RDB-Fc), and receptor-targeted monoclonal antibodies (mAb) (221).…”
Section: Antibody-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The virus entry block was studied for acting both in the cell receptor ACE2 and directly on the virus (neutralizing antibodies [nAbs]), specifically in the S1 subunit of the S protein (218)(219)(220). Regarding the blocking of ACE2 receptors, the application of some mechanisms stand out: the soluble version of ACE2 fused to an immunoglobulin Fc domain (ACE2-Fc), RDB domain attached to Fc (RDB-Fc), and receptor-targeted monoclonal antibodies (mAb) (221).…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…Aiming at reducing the hyper inflammation found in the lungs of SARS-CoV-2-infected patients, different clinical studies are currently investigating the activities of mAbs anti-JAK, anti-GM-CSF, anti-GM-CSF receptor, anti-M-CSF receptor, anti-CD14, anti-IFNg, anti-VEGF, anti-BKT, anti-CCR5, anti-IL-6, anti-IL-6 receptor, anti-TNFa, anti-IL1b, anti-IL1b receptor, and complement C5 inhibitor (220,251,252). Similarly, ongoing clinical trials have sought to reverse the hyper-thrombotic state found in critically ill patients by using anti-P-selectin, anti-CTGF, and factor XIIa antagonist mAbs (253,254).…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…Nonetheless, the United States Food and Drug Administration (US FDA) approvals have sped drug repurposing [ 20 ]. Medications now availalbe were developed to treat other viral infections [ 21 , 22 ]. However, newer drugs or drug formulations remain under development.…”
Section: Overview: Pathways Towards An Effective Covid-19 Vaccinementioning
confidence: 99%
“…Adaptive immune dysfunctions include lymphopenia and activation, granulocyte and monocyte dysfunction, and elevated immunoglobulin G (IgG) and total antibody levels [ 6 , 59 ]. These are present in blood and convalescent plasma of infected people [ 22 , 60 , 61 ]. Control of inflammation is achieved by immune modulation [ 22 , 62 , 63 ].…”
Section: Overview: Pathways Towards An Effective Covid-19 Vaccinementioning
confidence: 99%
“…It also uses transmembrane protease serine 2 (TMPRSS2) receptor to prime its spike (S) protein in target cells. 15,16 TMPRSS2 plays a role in influenza virus pathogenicity as well by cleaving hemagglutinin. 17 Other yet-unknown cellular entry modes might also be involved in SARS-CoV-2 infection, especially considering that only minimal percentages of leukocytes express ACE2.…”
Section: Interaction Of Sars-cov-2 With the Immune Systemmentioning
confidence: 99%